COVID-19 y el cierre de escuelas: Aportes de las ciencias sociales para la construcción de un currículo postcrítico desde el GEOFORO Iberoamericano - de Sousa Fernandes, Silvia Aparecida [UNESP]; Monteagudo, Diego García; Mena, Nancy Palacios (Curriculo sem Fronteiras, 2020)
The article discuss the conception that teachers and students of three iberoamerican countries (Brazil, Colombia and Spain) presents as school experiences and decisions facing the COVID-19 pandemic, by the analysis of the Foro 26 of GEOFORO – Iberoamerican Forum of Education, Geography and Society. It intends to achieve a dual goal: on the one hand, analyze the aspects that influence the conceptions about the pandemic in each country; on the other hand, know the speeches of the in-service and training teachers, in aspects that concerns the educational world since the iberoamerican context. We start from the afirmation that the challenges faced by the professors of basic education and the demands of remote education are bigger in the context of the current pandemic, since the social isolation and quarentine situation introduce new challenges for the implementation of syllabus and the development of educational practices. Therefore, new educational speeches, curricular adaptations and practices that should be considered in the construction of a curriculum to the Social Sciences teaching in the iberoamerican scope are produced, aiming the development of a critical citizenship.
Keywords: Curriculum; Educational policy; Educational strategies; GEOFORO; Teacher’s attitude